STRUKTUR PELAPISAN SOSIAL MASYARAKAT JAWA DALAM NOVEL GADIS PANTAI KARYA PRAMOEDYA ANATA TOIR - LILIANI, ELSE (LITERA, 2015)
<img src="data:image/png;base64,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